Association of the extent of myocardial ischemia with outcomes in patients with suspected coronary artery disease in Japan. Issue 5 (November 2022) - Kato, Takao; Momose, Mitsuru; Uemura, Yukari; Naya, Masanao; Matsumoto, Naoya; Hida, Satoshi; Yamauchi, Takao; Nakajima, Takatomo; Suzuki, Eriko; Inoko, Moriaki; Tamaki, Nagara
Abstract: Background: There is an ongoing controversy regarding the necessity of single-photon emission computed tomography (SPECT) for patients with ischemic heart diseases after the publication of the results of the ISCHEMIA trial. We aimed to evaluate the association of the extent of myocardial ischemia with outcomes in patients with suspected coronary artery disease in Japan. Methods: From the data of 2780 patients with stable angina who were enrolled prospectively between January 2006 and March 2008 in Japan and had undergone physician-referred non-invasive imaging tests (Japanese Coronary-Angiography or Myocardial Imaging for Angina Pectoris Study), 1205 patients managed with SPECT were stratified by 10 % myocardial ischemia. Major adverse cardiac events (MACEs), including death, myocardial infarction, hospitalization for heart failure, and late revascularization, were followed-up for 1 year. Results: Patients with ≥10 % myocardial ischemia ( n = 173) were less likely to be women than patients with <10 % myocardial ischemia ( n = 1032) and had a significantly higher 1-year cumulative incidence of MACEs (6.9 % vs. 1.8 %, p < 0.0001). After adjusting for confounders, the risk of ≥10 % myocardial ischemia relative to <10 % myocardial ischemia for MACEs remained significant [adjusted hazard ratio (95 % confidence interval), 2.40 (1.09–5.26), p = 0.029]. After adjusting including treatments, the risk of MACEs became insignificant between the ≥10 % myocardial ischemia group and the <10 % myocardial ischemia group [adjusted hazard ratio (95 % confidence interval), 1.04 (0.45–2.45), p = 0.92]. Conclusion: The presence of ≥10 % myocardial ischemia at diagnosis was significantly associated with the 1-year risk for MACEs in Japanese patients with suspected coronary artery disease. Graphical abstract: Unlabelled Image Highlights: Risk of ≥10 % ischemia was observed in coronary artery disease patients in Japan. After adjusting including treatments, the risk became insignificant. Because of the 1-year follow-up, the event rate was low.